Chemical and Thermal Investigation on Stability of Tanuma Formation Using Different Additives with Drilling Fluids - Khalid Mohammed Abdulzahra; Asawer Abdulrasul Kuery; Mayssaa Ali Abdul aoun (Journal of Engineering, 2020)
Wellbore stability is considered as one of the most challenges during drilling wells due to the reactivity of shale with drilling fluids. During drilling wells in North Rumaila, Tanuma shale is represented as one of the most abnormal formations. Sloughing, caving, and cementing problems as a result of the drilling fluid interaction with the formation are considered as the most important problem during drilling wells. In this study, an attempt to solve this problem was done, by improving the shale stability by adding additives to the drilling fluid. Water-based mud (WBM) and polymer mud were used with different additives. Three concentrations 0.5, 1, 5 and 10 wt. % for five types of additives (CaCl2, NaCl, Na2SiO3, KCl, and Flodrill PAM 1040) was used. Different periods of immersion (1, 24 and 72 hours) were applied. The results of the immersion test showed that using 10 wt. % of Na2SiO3 for WBM gives a high recovery percentage (77.99 %) after 72 hr, while the result of the dispersion test (roller oven) of 10 wt % of sodium silicate with WBM was (80.97 %) after 16 hr. Also, the immersion test result of 10 wt% of sodium silicate with polymer mud was (79.76 %) after 72 hr and the results of dispersion test (roller oven) of 10 wt. % of sodium silicate with polymer mud was (84.51 %) after 16 hr.